The investigation of the attitudes of students at the faculty of sports sciences towards human rights in sports according to different variables: Spor bilimleri fakültesi öğrencilerinin sporda insan hakları tutumlarının farklı değişkenlere göre incelenmesi - Soyer, Alptuğ; İbiş, Serkan and Güngör, Nuri Berk (Journal of Human Sciences, 2024)
The aim of this research is to examine the attitudes of students studying at the faculty of sports sciences towards human rights in sports in terms of different variables. The research group consists of 85 (41.1%) women and 122 (58.9%) men studying at the faculty of sports sciences. The data collection tools in the research are the personal information form and the Human Rights in Sports Attitude Scale. It was determined that the scores of the participants from the human rights attitude scale in sports were above the average. It was determined that the participants human rights in sports attitude scale and its subdimensions did not differ according to the gender variable. According to the participants’ department variable, a significant difference was detected in favor of coaching education only between coaching education and physical education and sports teachers in the subdimension of solidarity rights. Another finding of the research was that as the age of the participants increased, the values ​​they received from personal rights increased, and as the age decreased, the attitude towards social rights increased. As a result, people who are interested in the field of sports sciences attract wide attention with their popular lectures, seminars, and other elements regarding human rights in sports. (Extended English summary is at the end of this document) Özet Bu araştırmanın amacı spor bilimleri fakültesinde öğrenim görmekte olan öğrencilerin farklı değişkenler açısından sporda insan hakları tutumlarının incelenmesidir. Araştırma grubu spor bilimleri fakültesinde öğrenim görmekte olan 85 (%41.1) kadın ve 122 (%58.9) erkekten oluşmaktadır. Araştırmada veri toplama araçları ise kişisel bilgi formu ile Sporda İnsan Hakları Tutum Ölçeği’dir. Katılımcıların sporda insan hakları tutum ölçeğinden almış oldukları puanların ortalama seviyenin üzerinde olduğu tespit edilmiştir. Katılımcıların sporda insan hakları tutum ölçeği ve alt boyutlarının cinsiyet değişkenine göre farklılaşmadığı tespit edilmiştir. Katılımcıların bölüm değişkenine göre sadece dayanışma hakları alt boyutunda antrenörlük eğitimi ve beden eğitimi ve spor öğretmenleri arasında antrenörlük eğitimi lehine anlamlı bir farklılık tespit edilmiştir. Araştırmadaki bir başka bulgu ise katılımcıların yaşları arttıkça kişilik haklarından aldıkları değerlerin artış gösterdiği yaş azaldıkça sosyal haklara yönelik tutumun arttığı belirlenmiştir. Sonuç olarak spor bilimleri alanında öğrenim gören öğrencilerin sporda insan haklarıyla ilgili farkındalık düzeylerinin ders, seminer ve benzeri unsurlarla arttırılması gerektiği düşünülmektedir.